2019
DOI: 10.1111/jopr.13035
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Dynamic Virtual Articulation: Trueness and Precision

Abstract: Purpose To study the effects of altering condylar settings and pin openings on the trueness and precision of virtual articulators vs. mechanical articulators. Materials and Methods Maxillary and mandibular typodonts with fiducial markers were mounted on a mechanical Artex‐CR articulator, and the mandibular teeth were prepared to allow guidance solely by the posterior determinants of the articulator and the incisal table. The relationship of the mounted typodonts was preserved digitally by scanning using manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 30 publications
1
23
0
2
Order By: Relevance
“…The virtual contacts observed are more accurate than those obtained using an analogue approach, provided that the virtual procedure is performed with appropriate software and recording techniques 17,30‐33,35,36 . Additionally, virtual dynamic movements on a VA exhibit similar accuracy to those reproduced on a MA 34 . Virtual assembly in a VA will likely find indications in the study of cases that require repositioning of the arches in CR 37 .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The virtual contacts observed are more accurate than those obtained using an analogue approach, provided that the virtual procedure is performed with appropriate software and recording techniques 17,30‐33,35,36 . Additionally, virtual dynamic movements on a VA exhibit similar accuracy to those reproduced on a MA 34 . Virtual assembly in a VA will likely find indications in the study of cases that require repositioning of the arches in CR 37 .…”
Section: Discussionmentioning
confidence: 83%
“…The accuracy of different VA systems has been investigated, comparing the Dental Designer Software (v17.2.1; 3Shape, Copenaghen, Denmark) with a MA (Artex‐CR articulator; Amann Girrbach, Koblach, Austria). The data showed that the two systems produced similar results 34 . Some differences between registration systems in their ability to simulate mandibular movements have been reported, but the speed at which this technology is evolving makes scientific analysis difficult 3,34 …”
Section: Step 2: Accurate Occlusal Registration In Maximum Intercuspamentioning
confidence: 90%
See 1 more Smart Citation
“…Similar to a traditional mechanical articulator, a virtual articulator is an instrument to reproduce the position of the maxillary and mandibular dental arches, and to simulate the movement of jaw . Recently, many studies on a virtual articulator have been reported; however, most studies include mounting of the maxillary dental arch, or comparing the accuracy of articulation with a traditional mechanical articulator …”
Section: Discussionmentioning
confidence: 87%
“…The SCI values were measured as 43.50° on the left side and 45.50° on the right side by Christensen's method, and 44.25° on the left side and 46.17° on the right side by this technique. We speculate that the small difference in the SCI value is caused by the facebow transfer procedure and the positioning of the FH plane, than the articulation procedure . Compared to the arbitrary facebow transfer method, the position of the FH plane in this technique is closer to that of the kinematic facebow transfer method, which is a gold standard …”
Section: Discussionmentioning
confidence: 99%